Reflecting on the Place of Stories in Global Citizenship Education - Kofinti, Hilarius (Journal of Teaching and Learning, 2025)
This paper proceeds from the presupposition that stories could play a significant role in making children global citizens. I draw on Nussbaum’s (2008) theorization of narrative imagination to argue that telling children stories is one of the most appropriate ways to develop the values that would help them become global citizens. I argue that stories equip children with the appropriate dispositions to make meaningful contributions to the societies in which they find themselves. I also argue that stories offer teachers a viable method for making their classrooms culturally responsive. I conclude by suggesting that the ambiguity regarding which values to emphasize can be clarified by incorporating more stories into the classroom.